İbrahim el-Harbî ve hadis ilmindeki yeri - Sever, Ali (My University, 2018)
Hadis ilminin sistemleşip gelişmesinde önemli bir yeri olan Bağdat III./ IX. yüzyılın önde gelen ilim merkezlerinden biridir. Bu çalışmada belirtilen dönemde Bağdat’ta yaşayan İbrahim el-Harbî’nin hadis ilmine katkısı incelenecektir. Onun hayatına geçmeden önce genel olarak dönemin siyâsî ve ilmî ortamı hakkında bilgi verilmiştir. Biyografisi anlatılmış ve diğer İslâmî ilimlerdeki birikimine değinilmiştir. Harbî’nin, Ehl-i hadîs içerisinde Ahmed b. Hanbel’e yakın bir anlayışa sahip olduğu anlaşılmaktadır. Özellikle ricâl ilmi ve garîbü’l-hadîs konusunda dikkate değer katkısının olduğu görülmektedir. Bu durum sonraki çalışmalara etkisi açısından da incelenmiştir.

Baghdad which has a crucial role in the development and systematization of hadith science, is one of the most important scientific centres of 3rd century AH/ 9th century AD. In this study, the contribution of Ibrāhīm al-Harbī - who lived in Baghdad in the aforementioned period- to the hadith science will be examined. Information about the political and scientific environment of the period is also provided before his biography. Within the biography, his wide knowledge in other Islamic sciences is also mentioned. It is understood that al-Harbī has a comprehension which is closed to Ahmad bin Hanbal in Ahl al-Hadith. His valuable contribution to Ilm ar-Rijāl and Gharību alHadith is especially evident. This situation is also examined in terms of his effect on subsequent studies.
Keywords: Fıkhü’l-hadîs; Fiqh al-hadith; Garîbü’l-hadîs; Gharību al-Hadith; Hadis; Hadith; Ibrāhīm al-Harbī; Ilm ar-Rijāl; İbrahim el-Harbî Hadith; Ricâl İlmi